Molecular Characterization of Nitrogen-Containing Organic Compounds in Humic-like Substances Emitted from Straw Residue Burning - Wang, Y. J.; Min* Hu; Peng* Lin; Guo, Q. F.; ZJ Wu; Li, M. R.; L.M. Zeng; Y. Song; Zeng, L. W.; Y.S. Wu; Guo, S.; Huang, X. F.; et al. (Environmental Science & Technology Letters, 2017)
The molecular composition of humic-like[GRAPHIC]substances (HULIS) in different aerosol samples was analyzed using an ultrahigh-resolution mass spectrometer to investigate the influence of biomass burning on ambient aerosol composition. HULIS in background aerosols were characterized with numerous molecular formulas similar to biogenic secondary organic aerosols. The abundance of nitrogen-containing organic compounds (NOC), including nitrogen-containing bases (N-bases) and nitroaromatics, increased dramatically in ambient aerosols affected by crop residue burning in the farm field. The molecular distribution of N-bases in these samples exhibited similar patterns to those observed in smoke particles freshly emitted from lab-controlled burning of straw residues but were significantly different with those observed from wood burning. Signal intensity of the major N-bases correlated well with the atmospheric concentrations of potassium and levoglucosan. These N-bases can serve as molecular markers distinguishing HULIS from crop residue burning with from wood burning. More nitroaromatics were detected in ambient aerosols affected by straw burning than in fresh smoke aerosols, indicating that many of them are formed in secondary oxidation processes as smoke plumes evolve in the atmosphere. This study highlights the significant contribution of crop residue burning to atmospheric NOC. Further study is warranted to evaluate the roles of NOC on climate and human health.
Keywords: atmospheric aerosols; brown carbon; chemical-characterization; elemental composition; fine particulate matter; liquid-chromatography; nitrate radicals; pearl river delta; resolution mass-spectrometry; secondary formation